A Year After It Started: The Benefits of the Iraqi 4-H Program – A View from the Youth, Parents, and Volunteer Leaders of the Dar Al Salaam 4-H Club - Tim Kock; Chris J. Haynes; Justen Smith (Journal of International Agricultural and Extension Education, 2015)
In 2010, the United States Agency for International Development (USAID) Inma Agribusiness Program sought new avenues to enhance the agricultural sector and support democracy while working with marginalized and displaced people (USAID, 2011). The 4-H program was the vehicle to usher in change in the country. With the help of the national Iraqi 4-H leader, 25 young people (ages 8 – 16) were identified in the Babil area, based on the child’s desire to care for an animal and financial need of the families. The purpose of this qualitative ethnographic case study was to investigate the views of the youth, their parents, and the leaders of the first (USAID-Inma supported) 4-H club. The goal of the youth program was to strengthen the agriculture sector in the Babil area and increase family incomes, while instilling democratic values and providing young people hope and an opportunity to succeed. Data from this case study indicated youth from the Dar Al Salaam 4-H club embraced the idea of democracy, shared new ideas, inclusiveness in their actions, and yearned for change and a brighter future; positive indicators for any nation, developing or developed.
Keywords: Agriculture; Community; Iraq; 4-H Youth Development